Adverse Welfare Shocks and Pro-Environmental Behaviour: Evidence from the Global Economic Crisis - Artjoms Ivlevs (Institute of Labor Economics (IZA), 2017)
This paper examines the effects of the 2008–09 global economic crisis on people's pro-environmental behaviour and willingness to pay for climate change mitigation. We hypothesise that the crisis has affected pro-environmental behaviours through tightening of budget constraints and relaxation of time constraints. Using data from a large representative survey (Life in Transition II), conducted in 35 European and Central Asian countries in 2010, we find that people adversely affected by the crisis are more likely to act in an environmentally-friendly way, but less likely to be willing to pay for climate change mitigation. Our findings confirm the importance of time and budget constraints for undertaking pro-environmental action, and highlight a potentially positive role of adverse, external welfare shocks in shaping pro-environmental behaviour.
Keywords: G01; P28; Q53; Q54; 330; willingness to pay for climate change mitigation; pro-environmental behaviour; adverse welfare shocks; global economic crisis; transition economies